Fairy “tails”: flexibility and function of intrinsically disordered extensions in the photosynthetic world - Thieulin-Pardo, Gabriel; Avilan, Luisana; Kojadinovic, Mila; Gontero, Brigitte (Frontiers in Molecular Biosciences, 2015)
Intrinsically Disordered Proteins (IDPs), or protein fragments also called Intrinsically Disordered Regions (IDRs), display high flexibility as the result of their amino acid composition. They can adopt multiple roles. In globular proteins, IDRs are usually found as loops and linkers between secondary structure elements. However, not all disordered fragments are loops: some proteins bear an intrinsically disordered extension at their C- or N-terminus, and this flexibility can affect the protein as a whole. In this review, we focus on the disordered N- and C-terminal extensions of globular proteins from photosynthetic organisms. Using the examples of the A2B2-GAPDH and the α Rubisco activase isoform, we show that intrinsically disordered extensions can help regulate their “host” protein in response to changes in light, thereby participating in photosynthesis regulation. As IDPs are famous for their large number of protein partners, we used the examples of the NAC, bZIP, TCP and GRAS transcription factor families to illustrate the fact that intrinsically disordered extremities can allow a protein to have an increased number of partners, which directly affects its regulation. Finally, for proteins from the cryptochrome light receptor family, we describe how a new role for the photolyase proteins may emerge by the addition of an intrinsically disordered extension, while still allowing the protein to absorb blue light. This review has highlighted the diverse repercussions of the disordered extension on the regulation and function of their host protein and outlined possible future research avenues.